PARTICIPATION OF FAMILY DEVELOPMENT PROGRAM FOR FAMILY IN CHILDREN'S CARE AND GROWTH IN WEST JAVA - Dadang Suhenda; Roro Nurfauziah; Tatik Kusyanti (Poltekkes Kemenkes Bandung, 2020)
Since the launch of the BKB Program (1984), its implementation has not had a significant impact on changing childcare patterns and supporting family resilience programs. The study aims to determine families' participation in the care and development of children aged 0-6 years in members who have been exposed to the BKB program. The data used are secondary quantitative data and obtained from the results of the 2018 Accountability Program Performance Survey (SKAP). The survey was conducted in 27 Regencies / Cities in West Java Province. Data were analyzed univariate, bivariate, and multivariate. Respondents used were families with children aged 0-6 years, with a total of 10,731 respondents. Based on the results of the study showed that the number of families who had heard about BKB was less than families who had never been exposed to BKB information. The family participation rate in the care and development of children aged 0-6 years. Research variables are from all aspects (aspects of physical growth, issues of mental development, and points of social development) in families exposed to BKB information better than families who have never been exposed to BKB information. Variable Physical growth is the most dominant among other aspects (mental and social) towards family participation in care and development of children aged 0-6 years. A balanced promotion effort is needed between the three elements of parenting and child development so that the output can create and support family resilience programs. Keywords: Child Family Development (BKB), Care, Child Growth and Development, Children aged 0-6 years